Value of Emergent Neurovascular Imaging for “Seat Belt Injury”: A Multi-institutional Study - Sherbaf, F.G. (AJNR Am J Neuroradiol, 2021)
BACKGROUND AND PURPOSE: Screening for blunt cerebrovascular injury in patients after motor vehicle collision (MVC) solely based on the presence of cervical seat belt sign has been debated in the literature without consensus. Our aim was to assess the value of emergent neurovascular imaging in patients after an MVC who present with a seat belt sign through a large-scale multi-institutional study. MATERIALS AND METHODS: The electronic medical records of patients admitted to the emergency department with CTA/MRAs performed with an indication of seat belt injury of the neck were retrospectively reviewed at 5 participating institutions. Logistic regression analysis was used to determine the association among age, sex, and additional trauma-related findings with blunt cerebrovascular injury. RESULTS: Five hundred thirty-five adult and 32 pediatric patients from June 2003 until March 2020 were identified. CTA findings were positive in 12/567 (2.1%) patients for the presence of blunt cerebrovascular injury of the vertebral (n = 8) or internal carotid artery (n = 4) in the setting of acute trauma with the seat belt sign. Nine of 12 patients had symptoms, signs, or risk factors for cervical blunt cerebrovascular injury other than the seat belt sign. The remaining 3 patients (3/567, 0.5%) had Biffl grades I–II vascular injury with no neurologic sequelae. The presence of at least 1 additional traumatic finding or the development of a new neurologic deficit was significantly associated with the presence of blunt cerebrovascular injury among adult patients, with a risk ratio of 11.7 (P = .001). No children had blunt cerebrovascular injury. CONCLUSIONS: The risk of vascular injury in the presence of the cervical seat belt sign is small, and most patients diagnosed with blunt cerebrovascular injury have other associated findings. Therefore, CTA based solely on this sign has limited value (3/567 =  a 0.5% positivity rate). We suggest that in the absence of other clinical findings, the seat belt sign does not independently justify neck CTA in patients after trauma.